Need assessment for the deployment of an Institutional Repository at Mzumbe University - Kuzilwa, M.; Bea, G.; Mosha, G.; Ghasia, M (DRPS - Mzumbe University, 2024)
This study focused on understanding the need for establishing an Institutional Repository (IR) at Mzumbe University from the readers’ perspective. The study used a sample of 222 respondents comprising staff and students drawn from Mzumbe University's Main Campus, Dar es salaam Campus College (DCC) and Mbeya Campus College (MCC). The sample was selected using the purposive sampling procedure for the explicit purpose of obtaining information from the two main groups of respondents, that is, males and females. Both qualitative and quantitative data were collected using questionnaires, interviews and focus group discussions. Data were analysed using the content analysis procedure and Statistical Package for Social Sciences (SPSS) and results were presented in tables and figures showing descriptive statistics, mainly frequencies and percentages.